(3SDGd Mhd GdTgQ GdPi Jhaj ajg GdfHi Udi Gddg Ydjg hSde hGdELGHI Ydi Pdcs - (3CHhRjO GdaGSj , YHO GdQMef Hf YHO GdbGOQ Hf Ydj Hf CHj GdeMGSf jhSa GdaGSj,J (B1096 (3g` s
(3ChdgG (B:s
(3SjOi QVi Gddg Yfge bO HdZJ Yf HYV ef jhKb Hg eef cGf bHdfG hgh SjOi YHO Gddg Hf Ydi Hf WGgQ GdMSfi Cfg cGf jSei TgQ aHQjQ ef GdTghQ GdYLejI eRghW s
(3BNQgG (B:s
(3hHGddg fSJQTO hfYJVO hUdi Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B285 - (3U(B288s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B145s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B226 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B(259) s
Keywords: (3GdJGQjNs